Genetic studies on monthly test-day milk records in Sahiwal cattle - D, MONALISA; GANDHI, R S; RAJA, T V; SINGH, AVTAR; SACHDEVA, G K (The Indian Journal of Animal Sciences, 2014)
Data on 713 Sahiwal cows maintained at the Institute over a period of 49 years (1961–2009) were used to estimate the genetic and phenotypic parameters of first lactation 305- day or less milk yield and monthly test-day milk yields. The heritability estimates of first lactation 305–day milk yield and these 10 test day milk yields (6th, 35th, 65th, 95th, 125th, 155th, 185th, 215th, 245th and 275th day) were 0.3581, 0.0489, 0.2621, 0.2723, 0.2204, 0.1802, 0.2927, 0.2585, 0.3122, 0.3645 and 0.3492, respectively. All the heritability estimates were statistically highly significant except for 6th and 125th day test-yields. The genetic and phenotypic correlations of majority of test day milk yields with first lactation 305-day milk yield were higher, positive and highly significant. Higher estimates of genetic and phenotypic correlations amongst test-day milk yields and their higher association with first lactation 305-day milk yield as well as higher estimates of heritability of all these traits revealed that all the milk yields (test days and FL305DMY) can be used to evolve multi trait selection criteria for cow/sire evaluation in Sahiwal cattle.